TRADISI MINAHASA TERKAIT DENGAN MAKANAN TRADISIONAL - Pamantung, Rina Palisuan (Universitas Sam Ratulangi, 2019)
Food is regarded as important aspects of indigenous culture of Minahasa when viewed from various Minahasa cultural relics that still survive today. In addition, specific Minahasan traditional food is associated with social behavior which is very typical for a particular event in the culture, but still rarely written scientifically, especially in the field of linguistics.Empirical evidence shows that there is an ambiguity (overlap) on the appearance of the name ofÂ typical food Â Â betweenÂ the party menu which still contains the original culture of Minahasa like Endo wangko 'holy day'Â or